2013
DOI: 10.1017/s1368980013000335
|View full text |Cite
|
Sign up to set email alerts
|

Associations among blood pressure, salt consumption and body weight status of students from south-western Ontario

Abstract: Objective: The purpose was to examine the associations among body weight status, blood pressure and daily Na intake among grade 7 students from south-western Ontario, Canada. Design: Cross-sectional. Data were collected using the Food Behaviour Questionnaire, including a 24 h diet recall. Measured height and weight were used to determine BMI. Blood pressure was taken manually using mercury sphygmomanometers. Setting: Twenty-six schools in south-western Ontario, Canada. Subjects: Grade 7 students (n 1068). Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 55 publications
(73 reference statements)
0
15
1
1
Order By: Relevance
“…However, we ruled out this possibility by measuring the sodium concentration in the serum and by excluding patients with hyponatraemia. There is evidence that sodium intake is linked to obesity and changes in body fat composition,19 and although obesity has been linked to MS risk, appear to occur in childhood and adolescence 20. Nevertheless, we included this variable in our adjusted models to account for potential confounding factors.…”
Section: Discussionmentioning
confidence: 99%
“…However, we ruled out this possibility by measuring the sodium concentration in the serum and by excluding patients with hyponatraemia. There is evidence that sodium intake is linked to obesity and changes in body fat composition,19 and although obesity has been linked to MS risk, appear to occur in childhood and adolescence 20. Nevertheless, we included this variable in our adjusted models to account for potential confounding factors.…”
Section: Discussionmentioning
confidence: 99%
“…A recent Korean study demonstrated that the estimated 24-hour urine excretion of sodium, which was used as a surrogate of sodium intake, is associated with MetS and its components [ 25 ]. Some studies conducted in pediatric fields have indicated that high sodium intake is related to obesity and hypertension [ 15 , 26 , 27 ], but few studies have evaluated the association of sodium intake with MetS and its components with the exception of elevated BP. In this study, after adjusting for confounders, we performed multivariate logistic regression analyses and demonstrated that boys with a U-Na to U-SG ratio in the highest quartile exhibited significantly higher risks for elevated TG and MetS compared with those with a U-Na to U-SG ratio in the lowest quartile.…”
Section: Discussionmentioning
confidence: 99%
“…Вейнбергер [44], который изучал сольчувстви-тельность, установил, что среди лиц с нормальным АД моложе 30 лет сольчувствительными являются 35%, и это делает чрезвычайно важным изучение потребления пова-ренной соли среди молодых людей. Как показывают ис-следования [45][46][47], в том числе и наше, досаливают при-Таблица 4. Распространенность регулярного и нерегулярного курения среди студентов двух вузов Москвы (в %) Примечание.…”
Section: таблица 1 распределение студентов двух вузов москвы по полоunclassified